Nilai Ekonomi Daur Ulang Sampah TPA Benowo - Andreas Kevin (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
TPA Benowo is the final waste processing site for the City of Surabaya. The process economic value related to the landfill gas power plant system is 314 billion. This study aims to determine the economic value of the waste recycling process through a landfill gas power plant system and the feasibility of investing in a Landfill Gas Power Plant by PT. Sumber Organik with the Surabaya City government. This study uses the cost benefit analysis method to determine whether the investment is feasible or not. The results of the study showed that the NVP value was RP. 184,230,806,134.32, the IRR value is 21.61%, the BCR value is 2.88, and PP is 2 years 7 months. It can be said, the investment made by PT. Organic Source meets eligibility to implement.